MACROECONOMIC IMPACT OF ISLAMIC BANK FINANCING IN SAUDI ARABIA - Fatima Abalhareth; Shabir Hakim; Jamaldeen Faleel (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Islamic banking is a fast-growing segment of the financial system in Saudi Arabia and has effects on the economic performance of a great importance to the economic growth. This study is to assist bridging an existing research gap of exploring how the Islamic banking helps the macroeconomic growth of K.S.A. The study mainly to employ the statistical analysis to investigate the macroeconomic impact of Islamic bank financing (IBF) in the Saudi economy from the year of 2001 to 2017 by looking into independent variables of the IBF and the total financing against the macroeconomic factors: inflation, unemployment, IT, GFCF, and GDP growth. The analyzed data are obtained from banks cope websites, Bloomberg and IMF. The main results from the VAR model in the E-Views show both of the TF and IBF have an impact on GFCF, but not on the inflation. The IBF effects on the unemployment and IT, but no significant effect on the GDP growth.